Analisis Implementasi Higiene Dan Sanitasi Di Pasar Kemiri Muka Kota Depok - Cindy Amelia; Susaldi Susaldi; Rosidi Roslan (Jurnal Kesehatan Lingkungan, 2021)
A traditional market is a form of public activity that should concern to the health aspect of environmental sanitation. That is an important thing to be applied in public places, including the market. There are still many environmental sanitation problems found in the market, one of which is the problem of poor sanitation facilities. This study aims to analyze the Implementation of Environmental Hygiene and Sanitation at the Kemiri Muka Market in Depok City in accordance with the Minister of Health Regulation No. 17 of 2020 concerning Healthy Markets. The research is descriptive and qualitative with data collection techniques in the form of in-depth interviews, observations, and assessment sheets. Informants in this study amounted to 14 people who were determined using the purposive sampling technique. The results showed that the facilities infrastrucutre and environmental sanitation did not meet the requirements because they only got the yes category as many as 53 points. Moreover, repairing or adding facilities and infrastructure and environmental sanitation is needed for environmental health in order to improve the degree of human health. This research is expected to produce research products in the form of scientific articles that will be published in indexed journal